Financing of Non-Communicable Disease Prevention in LMICs: Zambia, Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: To estimate spending on Non-Communicable Disease prevention in Zambia and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organisational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorized into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Zambia spent an estimated ZMK 47.06 million (US2.62 million) on population-level preventive healthcare in 2016, almost exclusively allocated to infectious diseases. Spending on NCD prevention is not separately budgeted in health budgets, reflecting its low prioritization. Zambia’s low focus on NCDs reflects its historical infectious disease burden, particularly the HIV/AIDS epidemic. Despite entering an epidemiological transition towards NCDs, there is still inadequate focus on NCD prevention and control. Challenges include a lack of NCD prevention in primary care, donor dependent health budgets, no institutional coordination mechanism for NCDs, low budgetary utilization and government concerns about public opposition to taxation and threat to domestic tobacco growers. Conclusion: Zambia’s health system remains predominantly dedicated to fighting infectious disease, with limited focus on NCDs and even less so on NCD prevention. Zambia needs to build on its successes against IDs and devise an integrated strategy for surveillance, prevention and control for ID and NCDs. Keywords: Noncommunicable Diseases, Tobacco, Behaviour, Immunodeficiency Syndrome, Employees, Incidence, Health Care, Risk Factors, Diet, Taxes